Draft Annual Plan 1990-91 Union Territory of Delhi Part 1-Outline - Planning Commission (Planning Commission, 1990)
The Metropolitan city of Delhi has been constantly striving for multi-dimensional growth. The ’Mini India' reflected in the composition of Delhi's population is vibrant in its thought process, actions and life pattern and it is the onerous responsibility of Delhi Administration to conceive, project and implement the developmental aspirations of Delhi’s citizens. The identification of thrust areas, priority sectors, building up of social action . plans, innovations in developmental areas and plan activities and establishing ideal trends for an infrastructure with long term sustaining capacity have always been accepted by Delhi Administration as its fundamental responsibility towards Delhi’s citizens. It is in this background that the Annual Plan proposals for 1990-91 have been formulated. The needs and priorities for the National Capital can be said to be substantially different from those meant for other parts of the country. Our experience over the last 3 decades has also shown that growths of output end employment in Delhi have substantially crossed the corresponding rates in the country as a whole. Infact, the employment generation potential of Delhi and the availability of higher income have attracted lot of people to Delhi from all over the country. Consequently, Delhi’s problems have registered a sharp increase and we are constantly striving to find solutions
Planning Department Delhi Administration, Delhi
Keywords: Agriculture I Allied Services; Minor Irrigation; Science; Technology Environment; General Eco Services; Survey E Statistics; Civil Supplies; General Education; Sports £ Youth Services; Labour; Labour Welfare; Social Welfare